KEPEMILIKAN BANK DAN KEPATUHAN REGULASI TERHADAP RISIKO PERBANKAN YANG DIMODERASI OLEH CHARTER VALUE - Taswan Taswan (Jurnal Keuangan dan Perbankan, 2012)
This papers first issue concerned the influence of bank ownership on the risk, the effect of regulation on thelevel of risk, and the effect of charter value on risk. Ownership relations to regulatory compliance on risk weremoderated by the charter value. By using a sample of commercial banks operating in Indonesia, and performedtesting with the MMR model, the result obtained was that domestic private ownership, foreign ownership andownership concentration had significantly positive effect on the risk. Each relationship was moderated by thecharter value. Charter values negatively affected the level of risk. This finding was consistent with theentrenchment argument. While regulatory compliance negatively affected the risk, but not moderated by thecharter value. Regulatory influence on the risk of convergence was consistent with the argument.